'I see their hatred'. Ethics of witnessing and The Missing Image – an intervention in Austria's Holocaust memory space. (2nd April 2020) - Popescu, Diana I.
ABSTRACT: The film installation by visual artist and filmmaker Ruth Beckermann, The Missing Image (2015) uses historic archival footage to re-configure the meaning of a contested memorial in central Vienna, Memorial against War and Fascism (1988–1991) by Austrian artist Alfred Hrdlicka. Based on first-hand research, field observations and interviews with contemporary visitors, this article interprets The Missing Image as representative of a counter-archive memorial intervention which facilitates ethical acts of witnessing and which, in their turn, help re-frame and correct public understandings of compromised war monuments. The article offers an account of how viewers create meaning out of their experiences of witnessing difficult visual material. In doing so, I emphasize the importance of empirical reception studies to understand more deeply the impact of public art and of memorial art interventions on contemporary audiences.